Manfaat Bimbingan Kelompok dalam Meningkatkan Etika Komunikasi Siswa - Enny Fitriani; Edy Zulfikar (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2018)
The technological advances that lead to the waning of eastern culture and the disintegration of the norms of politeness in every way, thus exert a bad influence on society, especially students, because adolescence is a transitional period of adolescent children making their emotions volatile or unstable. This is why teenagers are easily influenced in everything, so their ethics of communicating has faded. This research is to know the benefit of group guidance in improving student communication ethics, this research is categorized into pre experimental research (Pre-Experiment Design), with experimental design used in this research is The One Group Pratest Posttest. This study involves two types of variables. The free variables are Group Guidance, the dependent variable is the Ethics of Communicating. The instruments used in this study were the questionnaire of communication ethics as well as group guidance services and were analyzed using descriptive statistics.